2023
DOI: 10.3390/ma16062514
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Chlorine Influence on the Corrosion of Three Steels to Be Used in Water Treatment Municipal Facilities

Abstract: Many municipal facilities, such as pools and drinking water treatment facilities, are subject to ongoing maintenance due to the corrosion of their metallic materials caused by chlorine, leading to high costs and a possible risk to public health. A proper study of the employed product’s effect could lead to the use of better materials, which significantly increase the lifetime of metallic equipment more attacked by corrosion, through studies evaluating their cost-effectiveness. This paper was carried out with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Research reported that sodium hypochlorite or other chlorine-containing disinfectants impact corrosion of the steel after disinfection [ 31 ]. Similar results obtained research [ 30 , 32 , 33 ]; the sample immersed in 5% NaClO for three weeks presented corrosion, a phenomenon that is explained by the beginning of the corrosion in the materials. Water quality analysis were selected: pH, turbidity, residual chlorine, potassium ion, calcium hardness, total hardness, conductivity, total iron, chloride ion, and suspended matter.…”
Section: Resultssupporting
confidence: 90%
“…Research reported that sodium hypochlorite or other chlorine-containing disinfectants impact corrosion of the steel after disinfection [ 31 ]. Similar results obtained research [ 30 , 32 , 33 ]; the sample immersed in 5% NaClO for three weeks presented corrosion, a phenomenon that is explained by the beginning of the corrosion in the materials. Water quality analysis were selected: pH, turbidity, residual chlorine, potassium ion, calcium hardness, total hardness, conductivity, total iron, chloride ion, and suspended matter.…”
Section: Resultssupporting
confidence: 90%
“…chlorine [27,28] and its reaction with metals [29]. These findings raise a concern about the adverse effects of chlorine and its compounds on the environment due to the intensive disinfection of public spaces and surfaces [30].…”
Section: Methodsmentioning
confidence: 99%
“…An impact on aquatic fauna was detected at low chlorine concentrations (0.1 mg/L) [26]. Outdoor disinfection using sodium hypochlorite also causes surface corrosion due to the strong oxidizing features of chlorine [27,28] and its reaction with metals [29]. These findings raise a concern about the adverse effects of chlorine and its compounds on the environment due to the intensive disinfection of public spaces and surfaces [30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, using radiation for sterilization has received low customer acceptance, and ultrasound has a low potential for decontamination ([ 60 , 61 , 62 ]). Chemical methods, for instance, using sanitizers such as chlorine, can make the stainless steel less receptive to biofilm formation, but it can lead to chemical reactions and residue [ 63 , 64 ]. Nowadays, new methods of controlling biofilm on the surface of food industry facilities, such as applying bacteriophages to control biofilm formation, have attracted the attention of researchers [ 65 , 47 , 66 ].…”
Section: Introductionmentioning
confidence: 99%